Professional-applied Physical Training in the Professional Formation System of Police Officers - Costel GabrielȘCHIOPU (Editura Universitatii Transilvania din Brasov, 2022)
As a specific form of physical education, professional-applied physical training is an independent psycho-pedagogical process, aimed at ensuring specialized physical training on a continuous basis, towards a preferred professional activity, wishing to be an instructive process that completes the individual background of professionally useful psychomotor skills and abilities. Continuous improvement of motor, mental, moral, and volitional qualities depends entirely, directly or indirectly, on the person's personality, psychomotor ability, and the development of professional skills. The application of an efficient contemporary system of professional-applied physical training of police officers will produce major changes, which will be useful in training and strengthening professional behavior during professional activity due to the simplicity, homogeneity, and efficiency of this method and principles of training. The professional-applied physical training ensures the quantitative and qualitative bio-psychomotor basis, which increases the morphofunctional indices through a complex as varied as possible of the means, methods, and principles specific to the activity of the police officers.